2016
DOI: 10.4103/0970-4388.175516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the video output of the dental operating microscope on anxiety levels in a pediatric population during restorative procedures

Abstract: There is a reduction in anxiety from the first visit to the second visit for restorative treatment when the DOM is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…Included articles were published between 2005 and 2018 and were conducted in Brazil, Chile, India, Iran, Mexico, Saudi Arabia, Thailand, and the USA . All included studies were published in the English language . Sample size ranged from 28 to 176 participants and participant age ranged from 4 to 16 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Included articles were published between 2005 and 2018 and were conducted in Brazil, Chile, India, Iran, Mexico, Saudi Arabia, Thailand, and the USA . All included studies were published in the English language . Sample size ranged from 28 to 176 participants and participant age ranged from 4 to 16 years.…”
Section: Resultsmentioning
confidence: 99%
“…The number of instruments used ranged from one to six, and most studies used three or more instruments . The most frequent instruments used were objective instruments, such as pulse oximeter and blood pressure cuff, which evaluate heart rate, oxygen saturation, and systolic and diastolic blood pressure …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sayed[20] concluded that projecting the visual output of the dental procedures is effective in distracting the child patient during the procedure and subsequently reducing dental anxiety. In contrast, Mishra[21] stated that the multimedia was not found to be significantly affecting the behavior of the child in dental operatory.…”
Section: Introductionmentioning
confidence: 99%